Impacts of using Aloe vera as a feed additive in aquatic animals feeding trials: A mini-review - Wei, Lee Seong; Tahiluddin, Albaris B.; Hadiana, Z.A.; Kamarudin, Ahmad Syazni; Mohammed, Arifullah; Mohamad, Nor Azra; Kian, Lau Kia; Wee, Wendy (Walter de Gruyter GmbH, 2025)
Abstract Aquaculture is the world’s fastest-growing food production sector. To ensure sustainable practices in this vital industry, integrating green feed additives is crucial. This review aims to recapitulate and discuss the current research on the effects of Aloe vera (AV) as a feed additive on the growth and health of various aquatic animals. AV has emerged as a promising green feed additive in aquaculture due to its multifaceted benefits. These benefits include enhanced growth performance, improved flesh quality, modulated hematological parameters, stimulated disease resistance, stress mitigation, and even masculinization effects in certain species. The review further elaborates on the sources and beneficial effects of AV’s bioactive compounds. A key focus is understanding the mechanisms of action of AV and its derivatives, alongside determining optimal dietary inclusion levels for aquatic animals. Previous studies indicate that optimal dietary doses of AV and its derivatives range from 0.0005% to 6% of the diet, while a concentration of 0.005% is recommended for bathing treatments. These beneficial effects are attributed to AV’s rich array of bioactive compounds, including phenolic acids, glucomannan, acemannan, emodin, and anthraquinone. Overall, the findings suggest that the dietary inclusion of AV and its derivatives at low levels holds significant promise for promoting growth and enhancing the health of farmed aquatic animals. However, it is equally important to note that excessive doses of AV and its derivatives can negatively affect aquatic animal production.